ENHANCING THE PRODUCTION OF BIO GAS AND BIO ELECTRICITY - DR.K G PURUSHOTHAM,; A.JENIFER,; DEBABRATA ACHARJEE,; NABAM DEB,; A.PANDIAN, (International Journal of Pharma and Bio Sciences, 2015)
This study is considered for enhancing the production of biogas and bioelectricity produced from sludge in Sewage water treatment plant –Chennai. The sewage water collected from 44areas in Chennai under the pipe lines of pump. Then the treatment of pretreatment, primary and secondary treatments are taking place for purifying the contaminated water. This treatment are used to reduce the organic loading, total suspended solids and grease, in secondary treatment the sludge thickened is formed .The sludge thickened are pumped to the digester by the way of top, middle and bottom of the pipe lines, continuously the sludge mixed well, Alternatively the digester maintains at ideal condition and flow of mixing conditions .In this stage we are adding the enzyme in the digester.Our Bio-Enzyme is having Trehalose it is specialized carbohydrate for developing growth factor Arechea bacteria which is sole responsible in the formation of Methane gas. Three processes are involved in this gas formation - Hydrolysis, acidogenesis and methanogenesis.,DDuring the process of methanongesis the methane gas (CH4)is formed. During that process the enzyme react with methanongesis process and enhancing the methane gas production. All the biogases collected and passed through the pipe line to the Gasholder. After that the gases passed through the scrubbing system for removal of H2S (Hydrogen sulphide gas). The volume of H2S measured it should be less 10%, and then the gas passed to the gas engine, the gas engine convert the gas energy to electrical energy.